THE RELATION BETWEEN FINANCIAL EDUCATION AND INVESTMENT DECISIONS IN INDONESIA: CASE OF INDONESIAâS EARLY INVESTORS - Noviana, Jane
Behavioral finance is a psychology-financial based theory to explain the anomalies of investor’s decision. In making decision, investors have preference in deciding uncertain outcome but there uncertain of circumstances that will influence investor’s decision-making process. Judgment under uncertainty is called the Expected Utility Theory. Later on, Kahneman and Tversky (1979) develop the Prospect Theory which filled the gap of the expected utility theory. Prospect Theory stated that investors would make decisions based on gain or loss instead of the final outcome. Investors also tend to analyze these events using personal judgment, which will lead to anomaly behavior. Study conducted by Katarachia and Konstatinidis (2013) shows the application of behavioral finance and correlate it with demography profile in financial education. The objective of the study is to determine whether financial student in Greece who are involve in stock market activity, performing irrational behavioral in making decision when being faced to difficulty or student still able performing rational behavioral. Irrational behavioral shows from that investor performing bias including: risk aversion, loss aversion, mental accounting, time discounting, the framing effect, overconfidence, gambler’s fallacy, herding, cognitive reflection and hindsight bias. This study is the research gap from the previews research because similar research hasn’t being conducted in Indonesia. The goal of this paper is to find out whether investors in Indonesia showing irrational behavior in making investment decision when being faced with dilemma. This research also differs from previous research by extending the scope. Indonesia has three class major in High School: science, social and language. Researcher wants to find out how financial education impacts to bias in making financial decision made by the investor. To achieve this goal, primary data will be obtained from online questionnaire given to investors in Indonesia. The questionnaire content will be used to identify and trace investor’s background and risk profile. Investors will also being faced to uncertain decision to seek the type of bias that they performed which is presented in behavioral finance theory. In addition, this research will also elaborate the data analysis using logistic regression. The result from this research is that although investors in Indonesia already had financial education, they still misled to make irrational decision and shows biases behaviors in their decision when facing financial dilemmas.